2020
DOI: 10.1109/jeds.2020.3017141
|View full text |Cite
|
Sign up to set email alerts
|

In₀.₅₃Ga₀.₄₇As/InAs Composite Channel MOS-HEMT Exhibiting 511 GHz fτ and 256 GHz f max

Abstract: An In0.53Ga0.47As/InAs composite channel MOS-HEMT exhibiting peak f = 511 GHz and peak fmax = 285 GHz is demonstrated. Additionally, another device exhibiting peak f = 286 GHz and peak fmax = 460 GHz is reported. The devices have a 1 nm / 3 nm AlxOyNz interfacial layer and ZrO2 gate dielectric on a 2 nm / 4 nm In0.53Ga0.47As / InAs composite channel with a modulation doped In0.52Al0.48As back barrier. To reduce parasitic gate-source and gate-drain capacitances, a modulation doped In0.52Al0.48As / In0.53Ga0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In order to enhance the RF performances, lateral scaling of the gate length is a straightforward approach to improve high-frequency performance such as f T , f max , and NF. [10][11][12] The previous report showed that the InP-based HEMT with high indium composition and an extremely short T-gate (25 nm) length demonstrated the stateof-the-art RF performance with f T of 610 GHz and f max of 1.5 THz. 13 However, the short channel effect is an issue that needs to be further addressed as the dimension of the device is scaled to the sub-100nm region.…”
mentioning
confidence: 99%
“…In order to enhance the RF performances, lateral scaling of the gate length is a straightforward approach to improve high-frequency performance such as f T , f max , and NF. [10][11][12] The previous report showed that the InP-based HEMT with high indium composition and an extremely short T-gate (25 nm) length demonstrated the stateof-the-art RF performance with f T of 610 GHz and f max of 1.5 THz. 13 However, the short channel effect is an issue that needs to be further addressed as the dimension of the device is scaled to the sub-100nm region.…”
mentioning
confidence: 99%